The Alteration of Coagulation in Patients with Thyroid Dysfunction - Akinci, Baris; Comlekci, Abdurrahman; A. Ozcan, Mehmet (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2011)
The influence of thyroid dysfunction on haemostasis is complex and still not very well understood. Both bleeding tendency and hypercoagulable states have been reported. In this article, we attempt to discuss the possible relationship between thyroid dysfunction and secondary haemostasis and fibrinolysis. After the analysis of the recent literature, we conclude that thyroid dysfunction is associated with alterations in fibrin generation and fibrinolysis. Most of the evidence suggests that hyperthyroidism is associated with impaired fibrinolysis and enhanced coagulation. Although, former studies proposed that there was an increase in fibrinolytic activity in hypothyroidism, increasing number of recent reports advocated the opposite. We believe that further prospective comprehensive clinical studies involving large numbers of patients either with overt or subclinical thyroid dysfunctions should be performed to clarify the effect of thyroid dysfunction on secondary haemostasis and fibrinolysis. Recent important patents focusing on coagulation and thyroid dysfunction are also discussed in this review.
Keywords: thyroid dysfunctions